Pendekatan Stem Terhadap Kemampuan Berfikir Kritis Abad 21 Siswa Kelas V Sekolah Dasar - Azni Izzah Ashar; Apri Irianto; Reza Rachmadtullah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Learning in elementary schools has to be implemented using methods that are in line with 21st century education goals. STEM is a viable solution for use in the implementation of learning because it places an emphasis on students' mastery of science, which in turn encourages students' critical thinking skills, allowing them to gauge their own learning progress. However, STEM (Science, Technology, Engineering, and Mathematics) education is still underutilized in elementary schools. Therefore, we want to examine how teaching subjects like Science, Technology, Engineering, and Math (STEM) affects primary school children's capacity for critical thinking in the twenty-first century. Quantitative methods of the experimental kind were used for this investigation. (quasi-experiment). The first phase in the data collecting procedure is the pre-test, followed by the treatment of both groups and finally the post-test. The results of this study show that there is an influence of the approach of science, technology, engineering and mathematics (STEM) on the ability to think critically of 21st-century elementary school students.